The hepatitis B virus envelope proteins: molecular gymnastics throughout the viral life cycle - Seitz, Stefan; Bartenschlager, Ralf (Annual review of virology, 2020)
New hepatitis B virions released from infected hepatocytes are the result of an intricate maturation process that starts with the formation of the nucleocapsid providing a confined space where the viral DNA genome is synthesized via reverse transcription. Virion assembly is finalized by the enclosure of the icosahedral nucleocapsid within a heterogeneous envelope. The latter contains integral membrane proteins of three sizes, collectively known as hepatitis B surface antigen, and adopts multiple conformations in the course of the viral life cycle. The nucleocapsid conformation depends on the reverse transcription status of the genome, which in turn controls nucleocapsid interaction with the envelope proteins for virus exit. In addition, after secretion the virions undergo a distinct maturation step during which a topological switch of the large envelope protein confers infectivity. Here we review molecular determinants for envelopment and models that postulate molecular signals encoded in the capsid scaffold conducive or adverse to the recruitment of envelope proteins.
Gesehen am 06.05.2022